145 Unplanned Reoperation After Craniotomy for Tumor: A National Surgical Quality Improvement Program Analysis. (August 2016) - Dasenbrock, Hormuzdiyar H.; Yan, Sandra C.; Chavakula, Vamsidhar; Gormley, William B.; Smith, Timothy R.; Claus, Elizabeth; Dunn, Ian F.
Abstract : INTRODUCTION: Although reoperation has been utilized as a metric of quality of care, no national analysis has evaluated the rate of, reasons for, and predictors of unplanned reoperation after craniotomy for tumor. METHODS: Patients who underwent cranial tumor resection were extracted from the prospective National Surgical Quality Improvement Program (NSQIP) registry (2012-2014). Multivariable logistic regression examined predictors of an unplanned cranial reoperation. Predictors screened included patient age, sex, tumor location and histology, functional status, comorbidities, preoperative laboratory values, and operative urgency and time. RESULTS: Of the 11 462 patients included, 3.1% (n = 350) underwent an unplanned cranial reoperation. The most common reasons for cranial reoperation were intracranial hematoma evacuation (21.4%), superficial or intracranial surgical site infections (11.6%), re-resection of tumor (9.8%), decompressive craniectomy (6.1%), and repair of cerebrospinal fluid leakage (5.6%). The strongest predictor of any cranial reoperation was preoperative thrombocytopenia (less than 100 000/µL, odds ratio [OR], 2.51; 95% confidence interval [CI], 1.23-5.10, P = .01). Thrombocytopenia, hypertension, emergent surgery, leukocytosis, and operative time greater than 300 minutes were predictors of reoperation for hematoma ( P = .004), while dependent functional status, morbid obesity, and longer operative time were predictors of reoperation for surgical site infections ( P = .03). Infratentorial location, American Society of Anesthesiologists (ASA) class 3 to 5 designation, dependent functional status, leukocytosis, and operative time greater than 300 minutes were all predictors of reoperation for ventricular shunt placement ( P = .02). Although any unplanned cranial reoperation was not associated with differential odds of mortality (OR, 1.68; 95% CI, 0.94-3.00; P = .08), hematoma evacuation was significantly associated with 30-day death (OR, 2.09; 95% CI, 1.03-4.25, P = .04). CONCLUSION: In this NSQIP analysis, unplanned cranial reoperation was primarily associated with operative indices, rather than preoperative characteristics, suggesting that reoperation may have utility as a quality indicator. Hypertension and thrombocytopenia are potentially modifiable predictors of reoperation for hematoma, which were associated greater odds of 30-day death.